Coal, energy and the environment in Pakistan - Durrani, Nasir Ali (Journal of Himalayan Earth Sciences, 1993)
Some major policy initiatives and decisions are needed to encourage the mining and utilization of indigenous lignitic quality coal resources of the country, particularly recently discovered Thar Parker mega-coal-deposits for power generation through investment by the private sector. As future coal utilization in the country is expected to rise manifold replacing petroleum products. This makes it mandatory for the environmental protection Agency of the country to formulate rules and regulations and strict controls for preserving the ambient air quality to Protect the ecological-system and human health, in and around the mining areas.